Frequency And Determinants Of Chronic Lower Back Pain Among Patients Presenting To Primary Care Clinics In Pakistan: A Cross-Sectional Analysis - Rabbiya Amir; Fatima Jehangir; Misbah Muhammad; Nida J. Ahsan; Tariq Adnan (Journal of Rawalpindi Medical College)
Objective: To ascertain the determinants of chronic lower back pain among patients presenting in primary care clinics.